Mediation Job Satisfaction : Leadership And Organizational Culture On Organizational Commitment - Ari Syamsul Bahri; Haekal Munawar; Windi Widayati; Sunimah Sunimah (Cita Konsultindo Research Center, 2024)
This research aims to determine the influence of leadership and organizational culture on organizational commitment and the influence of leadership and organizational culture on job satisfaction and whether job satisfaction can mediate leadership and organizational culture with organizational commitment. The method used in this research is to use quantitative descriptive methods. PLS-SEM model analysis for data processing. The sample used is Cluster Area Sampling, which is a profitability sampling method where the researcher divides a large population into small groups known as clusters and then randomly selects among the clusters to become the sample. So permanent employees were taken from the production department of PT. Arteria Daya Mulia, questionnaires were distributed to 319 employees and only 187 respondents returned the questionnaire or the survey response rate was 59.6%. It can be concluded several things as follows: (1) Leadership has a positive effect on job satisfaction; (2) Leadership has a positive effect on organizational commitment; (3) Organizational culture has a significant positive effect on job satisfaction; (4) Organizational culture has a significant positive effect on organizational commitment; (5) Job satisfaction has a significant positive effect on organizational commitment; (6) Job satisfaction mediates the influence of leadership on organizational commitment; (7) Job satisfaction mediates the influence of organizational culture on organizational commitment.